Application of BMP in Bone Tissue Engineering - Zhu, Liwei; Liu, Yuzhe; Wang, Ao; Zhu, Zhengqing; Li, Youbin; Zhu, Chenyi; Che, Zhenjia; Liu, Tengyue; Liu, He; Huang, Lanfeng (Frontiers in Bioengineering and Biotechnology, 2022)
At present, bone nonunion and delayed union are still difficult problems in orthopaedic. Since the discovery of bone morphogenetic protein (BMP), it has been widely used in various studies due to its powerful role in promoting osteogenesis and chondrogenesis. Current results show that BMPs can promote healing of bone defects and reduce the occurrence of complications. However, the mechanism of BMP in vivo still needs to be explored, and application of BMP alone to a bone defect site cannot achieve good therapeutic effects. It is particularly important to modify implants to carry BMP to achieve slow and sustained release effects by taking advantage of the nature of the implant. This review aims to explain the mechanism of BMP action in vivo, its biological function, and how BMP can be applied to orthopaedic implants to effectively stimulate bone healing in the long term. Notably, implantation of a system that allows sustained release of BMP can provide an effective method to treat bone nonunion and delayed bone healing in the clinic.